The research library multi-gallery - Zakaria, Khasiah; Talib, Faridah; Hashim, Rugayah; Jalaluddin, Jamizan (Universiti Teknologi MARA, Kedah, 2017)
University researchers and innovators require a multitude of support functions from the administrative departments especially the library. With research and innovation playing a crucial role in making or breaking a university’s world ranking, having a systematic support of galleries will ensure fast, accurate information for these academics through an innovative system. Realizing the need for such a customized system, Universiti Teknologi MARA Selangor (UCS) took the initiative to plan, analyze, design and implement the system of galleries to accommodate and assist the researchers. Therefore, the objectives of this innovation, the is to reimagine customer experiences through intuitive, personalized and effective support functions, to leverage big data through improved services, and to strengthen the communities served. With these considerations in mind, a comprehensive study was undertaken of what composes a physical learning environment. This would seem to consist of four learning contexts: social, individual, formal teaching and informal learning processes. These elements form an interactive whole in which the physical learning environment plays a central role in reforming the university’s operational culture; it should be analyzed and developed holistically. This study approaches the subject by considering the learning space and its functioning environment as such. Within it, flexible and adaptable innovative and research spaces and their related learning environments are formed through multidimensions.